357 SKIN TEST REACTIVITY OF SHRIMP-ALLERGIC SUBJECTS TO INHALANT AND OTHER FOOD ALLERGENS. (1st January 2005) - Reder, M. W.; El-Dahr, J. M.; Wild, L. G.; Bucci, L.; Demerell, D.; Soteres, D.; Villacis, J.
Abstract : Rationale: Shrimp is a major seafood consumed in the U.S. and also an important seafood allergen. The major shrimp allergen is the muscle protein tropomyosin, which is present in other inhaled and ingested allergens. Thus, it was of interest to determine potential sensitivity of shrimp-allergic subjects to these other allergens. Methods: Shrimp-allergic subjects were recruited by advertisement. 58 subjects (25 male, 33 female) ages 18-63, with definitive histories of shrimp allergy, as determined by questionnaire, were selected. Subjects were skin prick tested (ST) with aeroallergen and shellfish food extracts from Hollister-Stier; positive ST was determined by wheal with flare. IgE antibody responses to shrimp were measured by CAP-RAST. Results: 37/58 (64%) subjects were ST positive to at least 1 of the 2 shrimp extracts tested, 41 (71%) were positive to either crab, lobster, crawfish, or oyster, 51 (88%) to either cockroach or dust mite, 19 (33%) to tree pollens, and 14 (24%) to grass pollens. Of the 37 subjects ST positive for shrimp, 35 (96%) were positive to crab, lobster, or crawfish. 36 (97%) reacted to either cockroach or dust mite. Of the 58 original subjects, 28 (48%) had undetectable IgE to shrimp (class 0) on CAP-RAST analysis. Of the 37 shrimp ST positive subjects, only 10 (27%) had no detectable IgE to shrimp. Conclusions: Shrimp-allergic subjects showed significant reactivity to other shellfish, the greatest was to lobster (89%), the least to oysters (43%). Significant reactivity was observed to cockroach and dust mite extracts which is probably due in part to cross reactivity of invertebrate tropomyosin allergens. Better understanding of food and aeroallergen cross-reactivity should help improve diagnosis and therapy of food allergy.